Regulating “Pick One of Two” Practices in the Platform Economy: A Comparative Competition Law Analysis of Thailand and China - Nengjie Jiang; Pornchai Wisuttisak (Sriwijaya Law Review, 2026)
The rapid growth of food delivery platforms has made "Pick One of Two" practices a key issue in competition law enforcement. While both China and Thailand regulate "Pick One of Two" practices under their respective competition laws, the central challenge lies not in whether such practices should be regulated but in how competition authorities should determine whether they constitute competition law infringements. Drawing on the post-Chicago School as its theoretical perspective, this article examines the shortcomings of Thailand's competition law framework in determining the legality of "Pick One of Two" practices and explores how China's enforcement experience may inform improvements to Thailand's legal regime. The study adopts a doctrinal legal research method combining comparative legal analysis and case studies. It finds that Thailand's Trade Competition Act (TCA) suffers from deficiencies in determining market dominance, defining market power, distinguishing between the two concepts, and evaluating the competitive nature of "Pick One of Two" practices. In practice, the Trade Competition Commission of Thailand (TCCT) places excessive emphasis on market share while paying insufficient attention to network, lock-in, and competitive effects in the platform economy. This article proposes refining the legal criteria for determining market dominance, clarifying the relationship between market dominance and market power , and adopting an effects-based approach in enforcement.